Problem of Cultures Dialogue in Irish Poetry of the Second Half of the 20th - 21st Centuries - A. V. Kononova (Научный диалог, 2018)
The phenomenon of Irish poetry of the second half of the 20th - 21st centuries through the prism of the theory of dialogue of cultures is considered. It is noted that today in the domestic literary criticism there are only few works devoted to Irish poetry, especially its interaction with other literary traditions, so this aspect is estimated as one of the most promising areas of research. The article reveals the conditions and mechanisms for establishing cultural dialogue typical to modern Irish poets. In particular, the importance of translation not only as a method but also as a cultural metaphor is emphasized. The work of such authors as Seamus Heaney, Paula Meehan, Eavan Boland, Desmond O’Grady and others outstanding representatives of the Irish poetic tradition are involved. The author also highlights one of the key vectors of dialogue in the poetry of Ireland of the period under study - the dialogue with Russian literature, which is implemented in the works of Irish poets, including through their own translations. It is concluded that for many Irish poets the Russian literature acts as the “other,” allowing a better understanding of the surrounding reality and his- or herself. It is emphasized that the space of Russia and Russian literature becomes a part of the individual myth-making of Irish poets.